Chile : Request for an Arrangement Under the Flexible Credit Line and Cancellation of the Arrangement Under the Short-term Liquidity Line-Press Release; Staff Report; Staff Supplement and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report, 2022)
After an impressive recovery from the fallout of the Covid-19 pandemic, the Chilean economy is confronting an acute deterioration of the external environment. Downside risks have materialized, including a tightening of global financial conditions, a slowdown in global growth, and a substantial drop in Chile's terms of trade. Domestic economic policies are appropriately being recalibrated to mitigate risks and preserve macroeconomic stability, while supporting vulnerable groups. The authorities will continue leveraging on Chile's very strong fundamentals and policy frameworks to implement an ambitious reform agenda in a challenging external environment.